Transcription of Ehrlichia chaffeensis genes is accomplished by RNA polymerase holoenzyme containing either sigma 32 or sigma 70 - Liu, Huitao; Ohlen, Tonia Von; Cheng, Chuanmin; Faburay, Bonto; Ganta, Roman R. (My University, 2013)
Bacterial gene transcription is initiated by RNA polymerase containing a sigma factor. To understand gene regulation in Ehrlichia chaffeensis, an important tick-transmitted rickettsiae responsible for human monocytic ehrlichiosis, we initiated studies evaluating the transcriptional machinery of several genes of this organism. We mapped the transcription start sites of 10 genes and evaluated promoters of five genes (groE, dnaK, hup, p28-Omp14 and p28-Omp19 genes). We report here that the RNA polymerase binding elements of E. chaffeensis gene promoters are highly homologous for its only two transcription regulators, sigma 32 and sigma 70, and that gene expression is accomplished by either of the transcription regulators. RNA analysis revealed that although transcripts for both sigma 32 and sigma 70 are upregulated during the early replicative stage, their expression patterns remained similar for the entire replication cycle. We further present evidence demonstrating that the organism’s -35 motifs are essential to transcription initiations. The data suggest that E. chaffeensis gene regulation has evolved to support the organism’s growth, possibly to facilitate its intraphagosomal growth. Considering the limited availability of genetic tools, this study offers a novel alternative in defining gene regulation in E. chaffeensis and other related intracellular pathogens.
Citation: Liu, H., Ohlen, T. V., Cheng, C., Faburay, B., & Ganta, R. R. (2013). Transcription of Ehrlichia chaffeensis Genes Is Accomplished by RNA Polymerase Holoenzyme Containing either Sigma 32 or Sigma 70. PLOS ONE, 8(11), e81780. https://doi.org/10.1371/journal.pone.0081780
Keywords: Sequence motif analysis; Gene expression; DNA transcription; Gene regulation; Transcriptional control; Regulator genes